Jasmonic Acid Mediated Management of Necrotrophic Pathogen Alternaria Leaf Spot in Soybean - Wasule, D. L.; Ingle, Y. V.; Shingote, P. R.; Shinde, R. M. (International Journal of Bio-resource and Stress Management, 2023)
The Field trial was conducted during Kharif season for two consecutive years (July–October 2017 and 2018) at three different locations namely; Amravati, Yavatmal and Katol under Dr. Panjabrao Deshmukh Krishi Vidyapeeth., Akola, Maharashtra, India. The nine treatments were designed in randomized block design replicated thrice to determine the potential use of an elicitor for Alternaria leaf spot management compared with standard fungicide. The treatments include two foliar sprays of either abiotic elicitors alone namely Salicylic acid (SA) @ 100 ppm, Benzoic acid @ 100 ppm, Humic acid @ 1%, Jasmonic acid @ 100 ppm, Potassium nitrate (KNO3) @ 1% or biotic elicitors Trichoderma viride @ 1%, Pseudomonas fluorescens @ 1% alone or recommended fungicide Propiconazole 0.1% alone at crop flower initiation stage and at 60 days after sowing. Field trials results shows the Propiconazole 0.1% significantly superior in management of disease upto 44.72 % followed by Jasmonic acid @ 100 ppm in controlling the disease upto 40.01 % and was found at par with propiconazole 0.1% in respect to percent disease index, percent disease control and seed yield. Highest percent disease index and least percent disease control and yield recorded in control. Elicitor Jasmonic acids induce protective, therapeutic treatments reduced the severity of disease advocated suppressing necrotrophs pathogen Alternaria alternata, the eco–friendly alternatives to fungicides.